Renta básica de ciudadanía. Filosofía, Economía y Política. Basic income of citizenship, Philosophy, Economy and Politics - Raventós, Daniel (Papeles del Este, 2006)
Daniel Raventós contributes the article entitled “Basic Income of Citizenship, Philosophy, Economy and Politics”. The work has a clear interdisciplinary focus and establishes arguments about the minimum income all individuals should receive independent of the conditions in which they live and geographical disparities. The entire discussion is framed in journalistic language and expresses numerous points of opinion. Throughout the article a review is made of certain commonly held truths about the Basic Income and its main traditional discussion points. It is argued that the income level of a country should not be taken as indicative of the existence of Basic Incomes, and a model of micro-simulation is applied to analyse the origins and destinations of sources of finance and the applied Basic Incomes, distinguishing between population groups. The work concludes with philosophical arguments in favour of the universal establishment of a Basic Income - in its broadest sense - in the twenty-first century.